Sosialisasi Manajemen Finansial Untuk Meningkatkan Efektivitas Pengeluaran Penerima Manfaat Bantuan Sosial PKH Warga RW 7 Kelurahan Pacarkembang Kecamatan Tambaksari Kota Surabaya - Arief Willdane; Ika Korika Swasti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The Family Hope Program (PKH) is a conditional cash assistance program aimed at alleviating poverty in achieving family welfare. The sub-district of Pacarkembang, Tambaksari District, is a target object for recipients of financial management education to optimize control over the use of social assistance. The formulation of the problem studied is the use and strategy of financial management in increasing the effectiveness of spending for PKH beneficiaries in Pacarkembang Village, Tambaksari District, Surabaya City. The goal is to find out effective strategies in financial management. This study uses a qualitative approach, namely research that intends to understand the phenomenon of what is experienced by research subjects and data collection in this study uses the method of observation, socialization and documentation during socialization. Overall, the results of assistance and socialization regarding financial management for PKH beneficiaries have a significant effect on the effectiveness of the use of social assistance. Based on a business view, financial management has a good influence and change for people who are able to implement it. So that PKH social assistance beneficiaries can see the effectiveness of its use.